2010
DOI: 10.2134/agronj2010.0193
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Yield and Morphology of Three Fall‐Dormancy Categories Harvested at Two Phenological Stages in a Subtropical Climate

Abstract: Alfalfa (Medicago sativa L.) is the most important hay crop used in the dairy industry of the Po Valley, Italy, characterized by a subtropical climate with hot, humid summers and cool winters. Information is lacking as to selecting fall dormancy (FD) varieties adapted to the region and their response to intense harvest regimes. A 3-yr study was conducted to investigate the effect of two harvest regimes based on phenological stage (early bud and early flower) and three FD categories on productivity, canopy heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 37 publications
9
23
0
Order By: Relevance
“…The average plant height ranged from 66.77 cm (MSP 14) to 79.39 cm (MSP 1), which was similar to the results of Rimi et al (2010) who obtained a range of plant heights from 65.9 cm to 75.0 cm. The fastest growth was recorded after cuts in population MSP 16 (26.56 cm), which was not significantly faster than the values determined regeneration in populations MSP 9 and 1 (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…The average plant height ranged from 66.77 cm (MSP 14) to 79.39 cm (MSP 1), which was similar to the results of Rimi et al (2010) who obtained a range of plant heights from 65.9 cm to 75.0 cm. The fastest growth was recorded after cuts in population MSP 16 (26.56 cm), which was not significantly faster than the values determined regeneration in populations MSP 9 and 1 (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…Besides environmental differences between the studies, this appears in agreement with Hall et al (2004), who found no measurable long‐term effects due to seeding rates on alfalfa stand density. Moreover, the forage yields recorded during this experiment (Rimi et al, 2010) were comparable to those reported in other studies that used a lower seeding rate and/or plant density (Kallenbach et al, 2002; Lauriault et al, 2009; Wang et al, 2009). In the previously mentioned reports, similar productivity by alfalfa with lower stand density may have been obtained via higher no.…”
Section: Resultssupporting
confidence: 85%
“…Irrespective of FD rating and date (Table 2), the plots harvested at early flower had 11% more plants m −2 than those harvested at early bud, in the average of FD ratings and sampling dates (242 vs. 218 plants m −2 , data not shown). This difference in stand density between harvest regimes is consistent to the response of dry matter yield, since plots harvested at early bud also had low productivity (Rimi et al, 2010). Moreover, these results are similar to those of other studies where alfalfa harvested more frequently during the growing season had lower stand density (Sheaffer and Marten, 1990; Gramshaw et al, 1993; Ventroni et al, 2010).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations